Olfactory threshold values of C4VOE as test agents for measuring the olfactory capability - Sukardjo Sukardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
The preliminary clinical study on seven volatile agents and their olfactory threshold values of cadinum, camphora, capsaicin, carbon disulphide, vanilla, oleum menthae piperitae and ether has been performed. Their concentrations in solution and as a vapour could be measured by regression calculation. The olfactory detection threshold of these evaporated agents constituted the following concentrations: cadinum 0.12325/0.007968, camphora 0.01993/0.0045364, capsaicin 0.0118/0.0007573, carbon disulphide 0.02703/0.0066363, vanilla 0.01884/0.004255, oleum menthae piperitae 0.01228/0.002064, and ether 0.014801/0.0003613. These agents could be normally recognized by healthy volunteers.The concentration of the agents can be drawn and displayed in linear graphic by arithmetic logarithm with 30% different vapour concentration for each agent. These volatile agents as test materials, based on these findings were called "C4VOE-GAMA Olfactometer". A clinical study to fmd out the normal standards of the olfactory threshold and the use of this test material in measuring the olfactory capability in cases of nasal pathology is suggested.Key words : C4VOE-LAMA olfactometer-volatile agent-olfactory threshold value-gas chromatograph